Error resilient video transmission over ATM networks. - Cuenca, P. (IEEE Communications magazine)
In the transmission process of a variable bit rate video signal over an ATM network, cells are inevitably exposed to delays and losses due to the statistical multiplexing used in these networks. These phenomena affect the quality of the video signal, and without adequate measures to control the propagation of impairments, the quality of service may fall below acceptable levels. We introduce a set of control mechanisms at different levels of the protocol architecture to support MPEG-2 based video communications systems using ATM networks as their underlying transmission mechanism. We argue that in order to be able to create video systems able to cope with cell losses encountered in computer communications systems, a structured set of protocol mechanisms is required. Our results show the effectiveness of the proposed set of mechanisms in improving the robustness of the video delivery system